THE ESSENCE OF VILLAGE AS A CONSTITUTIONAL GOVERMENT ORGAN IN STATE MANAGEMENT SYSTEMS - Muhammad Mashuri (Universitas Pendidikan Nasional, 2020)
Historically, all local communities in Indonesia have strong local wisdom which contains a spirit of sufficiency, balance and sustainability, especially in managing natural resources and people. It is philosophically clear that before governance over it existed, the Village first existed. The purpose of this research is to elaborate on the village as the basis and part of the governance arrangement afterward. A village that has an older government system should also be the spearhead in every administration of government, development and community affairs. The research used in this study is normative research using secondary data such as statutory regulations, legal theory, expert opinion, and court decisions. The approach that the writer uses is the approach of the Invitation Laws and the conceptual approach. The result of this paper is that Village autonomy and democracy which will be framed by a law on villages is not just an institutional matter, but has a deep philosophical basis. Efforts to strengthen regional autonomy and